Negotiating pharmaceutical uncertainty - Saethre, Eirik; Stadler, Jonathan (London Vanderbilt university press, 2017)
"Contrasting the development of innovative biomedical technologies with the everyday lives of female South African clinical trial participants, Negotiating Pharmaceutical Uncertainty illustrates how the uncertainty of transnational medical research unintentionally fosters women's control over their health, sexuality, and sociality"--Provided by publisher.
Infested natives and empowering biotechnologies -- Testing hope -- Recruiting meaning -- Libidinous sociality -- Experiencing efficacy -- The biotechnical salvation of a failed pharmaceutical.
Keywords: Women; Clinical trials; Human experimentation in medicine; Drugs; HIV infections; Biotechnology